Exploring Gender Dynamics in Hajj Research: A Bibliometric Review - Rosana, Sakinah Sofia; Azizah, Nur; Edayanti, Edayanti (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
Hajj is not only a religious ritual but also has social, economic, and political dimensions. Although, according to Sharia, the rituals of worship carried out by female pilgrims are the same as those of male pilgrims, from a gender perspective, the experiences, access, and challenges faced by female pilgrims are different from those of male pilgrims, including the physical-biological, cultural, and security threats, and even from the regulatory aspects of the hajj. This article, therefore, aims to analyze the gender dynamics that influence and are influenced by the hajj. The methodology used in this study is a qualitative approach complemented by descriptive statistical literature observations of 68 publications on the topic of hajj and gender. According to the findings, over 38 years, the number of documents on the hajj has been quite large (2320), but only 68 documents related to gender aspects. However, the discussion of gender aspects continues to increase, with a peak of nine publications in 2022 and seven publications in 2023. This increase indicates increasing recognition of gender dynamics in religious practices, the increasing global Muslim population, feminist and gender studies, accessibility of digital archives, and socio-political changes in various Muslim-majority countries. The largest number of publications came from Arabia, followed by the United States. Non-Muslim countries such as Australia, England, Canada, and Germany have made major contributions to integrating gender aspects into Islamic studies, including studies on the hajj. This study also exhibits that gender dynamics in Saudi Arabia after the launch of Saudi Vision 2030 have had a major impact on the implementation of a more inclusive and women-friendly hajj, especially related to the relaxation of provisions related to